Appointed public officials and local favoritism: Evidence from the German states - Thushyanthan Baskaran; Mariana Lopes da Fonseca (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We study the local favoritism of appointed German state ministers. Matching hand-collected data on ministers' place of residence to a sample of more than 8,000 west German municipalities during the period 1994–2013, we find that the home municipality of a state minister experiences higher employment growth than control municipalities. Given the institutional context, this effect is ostensibly due to apolitical favoritism (home bias) rather than electoral considerations. We conclude that favoritism may lead to a distortion in the allocation of public resources even in contexts with strong political institutions.
Keywords: D73; H70; 330; Distributive politics; Favoritism; Employment growth